2019
DOI: 10.1002/cncr.32648
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death after breast cancer diagnosis: A US population‐based analysis

Abstract: Background The focus on noncancer causes of death in patients with breast cancer (BC) remains superficial. The objective of the current study was to assess and quantify causes of death after BC diagnosis. Methods In total, 754,270 women with BC in the United States who were diagnosed during 2000 through 2015 and retrieved from the Surveillance, Epidemiology, and End Results (SEER) program were studied. Standardized mortality ratios (SMRs) for causes of death were calculated. Results Of the included patients, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 37 publications
5
106
0
Order By: Relevance
“…As advances in treatment options continue to improve outcomes for women with early breast cancer, women with highly treatable early‐stage HR+ tumors are more likely to die of causes other than their early breast cancer 28 . A recent study showed that among women with breast cancer who died 10 or more years after their diagnosis, 60.9% died of noncancer causes, whereas 23.6% and 15.5% died of breast cancer and other cancers, respectively 29 . Even within the 5 to 10 years after the diagnosis, 48.4% died of noncancer causes, and regardless of the time since diagnosis, Black women had higher standardized mortality ratios for individual noncancer causes of death 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As advances in treatment options continue to improve outcomes for women with early breast cancer, women with highly treatable early‐stage HR+ tumors are more likely to die of causes other than their early breast cancer 28 . A recent study showed that among women with breast cancer who died 10 or more years after their diagnosis, 60.9% died of noncancer causes, whereas 23.6% and 15.5% died of breast cancer and other cancers, respectively 29 . Even within the 5 to 10 years after the diagnosis, 48.4% died of noncancer causes, and regardless of the time since diagnosis, Black women had higher standardized mortality ratios for individual noncancer causes of death 29 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that among women with breast cancer who died 10 or more years after their diagnosis, 60.9% died of noncancer causes, whereas 23.6% and 15.5% died of breast cancer and other cancers, respectively 29 . Even within the 5 to 10 years after the diagnosis, 48.4% died of noncancer causes, and regardless of the time since diagnosis, Black women had higher standardized mortality ratios for individual noncancer causes of death 29 . Noncancer causes include chronic diseases that, like cancer, are associated with advancing age, and many are obesity‐related: heart disease, stroke, diabetes mellitus, kidney disease, and hypertension 30…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have reported on the non-cancer causes of death among patients with various cancer (e.g. prostate [9], breast [10], and oropharynx [11]). Moreover, non-cancer causes of death in long-term bladder cancer survivors were also investigated in a previously published study [12].…”
Section: Introductionmentioning
confidence: 99%
“…During 10 years of follow-up, the non-BCSD rate of pN0(i+) and pN0(i − ) was as high as 71.33 and 79.00%, respectively. A study on the causes of death for FBC patients has confirmed that the main cause of death was not breast cancer but heart disease 5 years after the diagnosis, and the proportion of BCSD will gradually decrease ( 27 ). Therefore, for patients with early-stage breast cancer, it is very important to pay close attention to other non-cancer diseases, especially cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%